Exploring the beliefs and attitudes of private general practitioners towards national health insurance in Cape Town, South Africa - Sheena Mathew; Robert Mash (AOSIS, 2019)
Background: Private general practitioner (GP) participation in the national health insurance (NHI) is necessary to address doctor shortages and achieve universal health coverage. An in-depth understanding of GP's views on the NHI is needed to inform implementation strategies. Aim: To explore the beliefs and attitudes of GPs towards the proposed NHI system. Setting: Cape Town, South Africa. Methods: This was a descriptive, exploratory, qualitative study using semi-structured interviews. Eleven GPs were recruited using purposeful snowball sampling from different practices and communities. Thematic data analysis was conducted using the framework approach and Atlas.ti software. Results: Although GPs saw the need for NHI, they felt that the government was antagonistic towards the private sector and had not engaged in a dialogue. They were wary of integration into a nurse-led primary care system and of being coerced. They felt that the public sector lacked the necessary financial and administrative capacity, and were concerned about the level, efficiency and sustainability of reimbursement, and the criteria to be used to accredit practices. General practitioners anticipated that the NHI would favour multidisciplinary teams and group practices. They also had mixed ideas about the impact on practice with some expecting higher workloads, stress and costs with reduced quality of care, while others saw more comprehensive care, better incomes and increased patient satisfaction. Conclusions: While GPs are essential for the success of the NHI, there are many concerns regarding government policy, plans for implementation and the consequences for GP practice. Many of the concerns expressed could be tackled by greater policy dialogue and clarification.